Eduardo Luiz. Na ordem, a desordem : ampliando a experiência da representação em pintura - Soares, Maria Leonor Barbosa (2004)
The work of Eduardo Luiz has a quality of strangeness that is responsible for the links often found out with Surrealism, which he seemed determined to reject. Actually, the mystery and absurdity found in his images must be related with the contradictions he correspondingly explore in the system of pictorial representation (contrasting descriptions of space in the same composition, for instance), and understood altogether as a device to conveying meanings that serve an investigation about the nature of representation, painting techniques, plastic languages and communication. Considering that non-denotation is impossible, he attempted to create a system that imposes the denotation as protagonist, leading the observer to understand “the power of denotation over the things it stands for”. This paper concerns how Eduardo Luiz developed his provocative process of representation, which therefore allows the observer to expand the experience of perception.